20 Years after the First Magnetic Resonance Imaging Cuban Machine: A Physical Engineering and Biophysics Project - Cabal, C. (Revista Cubana de Física, 2011)
The premises, results and scientic, technological and social impacts of the Cuban whole-body Magnetic Resonance Machine project, are discussed. It is concluded that the Universities are excellent scenarios to develop such high- impact, multidisciplinary projects. In developing countries it is essential to nd ways and alternatives to establish tight, strong and durable links between physics and technology, resulting in economic outputs according to each country's priorities.